Sistema de medição de desempenho para operação e manutenção de parques eólicos no Brasil - Santos, Marllen Aylla Teixeira dos (2016)
This dissertation aims to propose a Performance measurement system (PMS) for operation and maintenance (O&M) of wind farms in Brazil. To this end, was performed a literature review on the characteristics of an PMS and performance measurement initiatives in power plants. This allowed the elaboration of Conceptual Model that has guided the field research and the Indicators Framework, which was validated in the Focus Group 1, for examining the objective, scope, applicability, adaptability and relevance of the indicators. The field research had as technical procedure case studies in seven companies, aiming to collect information for the development of the proposal. The existing performance management forms in the wind farms were analyzed and the Indicators Framework was evaluated as to its use and acceptance. The cases were conducted through interviews with managers of strategic and tactical levels, in addition to collections of records, reports and other documents and information from the web page. The analysis of the cases occurred for the triangulation of this information. The PMS propositions were structured in the Focus Group 2, in which was analyzed the dimensions, constraints and performance indicators, by the analysis of the proposal’s scope. The PMS includes four dimensions: Financial (7 indicators), Energy Generated (12 indicators), Operation and Maintenance (13 indicators) and People (2 indicators), sustained by the performance constraints Reliability of the prospecting’s study, Construction and Assembly Quality, Organizational Learning, Support Tools and Techniques and Supply Chain Coordination. The use of PMS enables decisions based on evidence and causing increased operational efficiency and performance optimization in O&M of wind farms.